Psychological Distress, Anxiety, Depression, and Associated Factors Among Nigerian Healthcare Workers During COVID-19 Pandemic: A Cross-Sectional Study - Olanrewaju Ibikunle Ibigbami; Olanrewaju Ibikunle Ibigbami; Adesanmi Akinsulore; Adesanmi Akinsulore; Tolu Opakunle; Champion Seun-Fadipe; Champion Seun-Fadipe; Olakunle Ayokunmi Oginni; Victor Ogbonnaya Okorie; Ibidunni Oloniniyi; Olushola Olibamoyo; Olutayo Olubunmi Aloba; et al. (Frontiers Media S.A., 2022)
Objectives: We determined the prevalence of psychological distress, and the associations between sociodemographic factors, anxiety, depression, COVID-19-related experiences, and psychological distress, among nurses and doctors in Nigeria.Methods: The study was a cross-sectional descriptive study, conducted over a month (1st of July-31st of July 2021) among 434 Health Care Workers (HCWs) [225 (51.8%) nurses and 209 (48.2%) doctors] from two tertiary health facilities in southwestern Nigeria. Binary logistic regression was carried out to determine the factors associated with psychological distress (dependent variable), while the independent variables were anxiety, depression, and COVID-19 experience-related factors.Results: The prevalence of moderate and severe psychological distress was 49.1% and 5.8%, respectively. Individuals who had the first degree had significantly lower odds (AOR: 0.43; p = 0.037) of experiencing psychological distress while being a nurse (AOR: 2.03; p = 0.014), higher levels of anxiety (1.28; p < 0.001), and depression (AOR: 1.17; p = 0.005) were associated with significantly higher odds of experiencing moderate to severe levels of psychological distress.Conclusion: There is a high level of psychological distress experienced by these health workers. Hence, they will benefit from strategies to reduce their distress.